Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.